2016
DOI: 10.1177/0363546516659305
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Injury Characteristics of Pitchers Entering the Major League Baseball Draft After Ulnar Collateral Ligament Reconstruction

Abstract: There was no difference in the rate of professional advancement among pitchers drafted by the MLB who had undergone UCLR as amateurs compared with controls. Both groups had similar statistical performance. Pitchers in the UCLR group had an increased risk of DL assignment but no increase in the number of days on DL or risk of DL placement for elbow injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 30 publications
2
29
1
Order By: Relevance
“…This finding is likely attributed to MiLB pitchers being generally younger with fewer years of professional baseball experience in comparison with MLB pitchers, such that MiLB pitchers with a history of UCL reconstruction would more likely have undergone surgery before professional play. Additionally, both Camp et al 4 and Wymore et al 19 demonstrated that pitchers with a history of UCL reconstruction as amateurs are increasingly being selected in the MLB draft. This may also contribute to the increased prevalence observed in MiLB from 2012 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is likely attributed to MiLB pitchers being generally younger with fewer years of professional baseball experience in comparison with MLB pitchers, such that MiLB pitchers with a history of UCL reconstruction would more likely have undergone surgery before professional play. Additionally, both Camp et al 4 and Wymore et al 19 demonstrated that pitchers with a history of UCL reconstruction as amateurs are increasingly being selected in the MLB draft. This may also contribute to the increased prevalence observed in MiLB from 2012 to 2018.…”
Section: Discussionmentioning
confidence: 99%
“…18 Although numerous studies have reported the epidemiology of UCL injuries at various levels of play (ie, high school, college, professional), no recent investigation specifically reported the incidence of elbow UCL in collegiate baseball players. 5,11,12,17,24,28 Before the first UCL reconstruction, introduced by Dr Frank Jobe in 1976, the chronic pain and instability associated with UCL injury were often career ending. Given the serious implications of elbow instability resulting from UCL injury among baseball players, the objective of this study was to achieve a better understanding of its epidemiology in this population.…”
mentioning
confidence: 99%
“…These findings are similar to previously published data. In 2016, in a series of 38 pitchers evaluated after UCLR and compared with a control group, Wymore et al 15 demonstrated statistically similar performance metrics between the cohorts in terms of velocity, wins, ERA, WHIP, games started, innings pitched, wins, losses, strikeouts, and batters walked. In 2018, Camp et al 4 conducted a large matched cohort comparison of 345 pitchers after UCLR and demonstrated a statistically higher likelihood of advancement to the MLB level in the UCLR group.…”
Section: Discussionmentioning
confidence: 97%
“…Even less is known about the ability of team physicians to perform a risk assessment, or “grade” these players, and how their ratings correlate with their future performance. Two previous reports by Camp et al 4 and Wymore et al 15 comparing drafted players after UCLR with matched controls demonstrated conflicting results, with patients in the postsurgical group performing either similarly or even better than matched cohorts. These reports on drafted pitchers recommended longer follow-up, more pitchers in future studies, an evaluation of the accuracy of subjective team draft grades, and evaluation by pitching role.…”
mentioning
confidence: 93%